Covenant in the Persian Period - Odimuko, Dike O. (My University, 2025)
This dissertation examines what shall be termed “shifts” in the covenant-making process. Using a comparative sociological method, the dissertation will explore these shifts and demonstrate that the causes for some of the shifts were sociological, and that covenant in Ezra–Nehemiah was the culmination of the Judean return migrants’ efforts to assert their Judean Identity. The study will first examine earlier Israelite covenants such as the Noahic, Abrahamic, Sinai, Davidic, and Phinehas’s, of which YHWH was the initiator of and an active participant in the covenant-making ceremony. A diachronic survey of covenants in Israel will demonstrate a role reversal (shift) in the covenant-making process, where humans are the main initiators of covenants and YHWH becomes a passive party. This shift is explicitly depicted in the covenant-making process in Ezra–Nehemiah. While some scholars insist that this role reversal does not indicate a shift per se, this work, in agreement with other scholars, will argue that there is indeed a definite shift in roles and demonstrate some sociological causes for them. It is important, however, to note that proponents of the shift claim do not give reasons for the shifts. So, to deal with this problem, this work will examine the social character of Yehud within the Persian Empire to unearth sociological factors that influenced the covenant-making process in Ezra–Nehemiah. While this dissertation’s focus is covenant as outlined in Ezra–Nehemiah, this study will potentially lead to the broader question of Persian influence on the Judean worldview in the Persian period.
Causes for Shifts in the Covenant-Making Process in Ezra–Nehemiah
Keywords: Ezra–Nehemiah; Covenant